Doing critical discourse studies with multimodality: from metafunctions to materiality. Issue 5 (20th October 2019) - Ledin, Per; Machin, David
ABSTRACT: In Critical Discourse Studies (CDS) and in other linguistics oriented scholarly journals we now see more research which draws upon multimodality as part of carrying out analyses of how texts make meaning, in order to draw out the ideologies which they carry. However, much of multimodality is itself based closely on one theory of language called Systemic Functional Linguistics (SFL). And despite calls from some scholars there has been no real interrogation of the concepts and models drawn from this theory as regards how suitable they are both for analyzing different forms of communication and for answering concrete research questions of the nature asked in CDS. In this paper we assess the core principles, taken from SFL into multimodality. Using examples we consider which are more or less suitable for the kinds of work we do in CDS. We make a case that SFL has a narrow notion of 'texts' and a weak notion of context. We show how we can address such problems to deal with what we call the 'materiality' of multimodal communication.